The Effect of Transformational Leadership Style and Job Satisfaction on Employee Performance - Basalamah, Muhammad Syafii A (Yayasan Pendidikan Bukhari Dwi Muslim, 2023)
Purpose: This study aims to analyze and determine the effect of transformational leadership style and job satisfaction on employee performance at PT Mandiri Utama Finance in Makassar City. The study hypothesizes that both transformational leadership and job satisfaction positively and significantly impact employee performance. Research Design and Methodology: The study population comprised 225 employees of PT Mandiri Utama Finance, with a purposive sample of 68 employees. Primary data were collected directly from respondents through questionnaires. The data analysis included descriptive statistics, validity and reliability tests, normality, multicollinearity, heteroscedasticity tests, and hypothesis testing using multiple linear regression, t-tests, f-tests, and coefficient of determination tests. Findings and Discussion: The results indicate that both transformational leadership style and job satisfaction have a positive and significant effect on employee performance, both individually and collectively. This suggests that enhancing leadership practices and fostering job satisfaction can significantly improve employee performance at PT Mandiri Utama Finance. Implications: The findings have important implications for organizational policies and practices, particularly in leadership development and employee engagement strategies. Future research could explore additional factors influencing employee performance and extend the study to different organizational settings to enhance the generalizability of the results.